2001
DOI: 10.1002/1521-3803(20010601)45:3<150::aid-food150>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic aspects of theMaillard reaction: a critical review

Abstract: The literature concerning the kinetics of the Maillard reaction was critically discussed according to the initial, intermediate and advanced stages, as this is the way the Maillard reaction is traditionally analysed. For each stage, a division is made between simple kinetics and complex kinetics. Simple kinetics means that the general rate law is used and results are reported as zero-, first- or second-order reactions (sometimes a fractional order). It is emphasized that this approach for a complex reaction as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
218
1
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(241 citation statements)
references
References 37 publications
18
218
1
4
Order By: Relevance
“…Actually it was difficult to distinguish between a first-order and second-order kinetics at 50 C but we preferred the latter because of a better fit. Different trends in kinetic parameters according to the heating temperatures applied which affect the activities of reactants can be result of differences in temperature sensitivity of various reaction steps in Maillard reaction (Van Boekel, 2001). A similar phenomenon for HMF formation in honey heated at 50-100 C has been reported (Fallico et al, 2004).…”
Section: Kinetic Calculationsmentioning
confidence: 56%
See 1 more Smart Citation
“…Actually it was difficult to distinguish between a first-order and second-order kinetics at 50 C but we preferred the latter because of a better fit. Different trends in kinetic parameters according to the heating temperatures applied which affect the activities of reactants can be result of differences in temperature sensitivity of various reaction steps in Maillard reaction (Van Boekel, 2001). A similar phenomenon for HMF formation in honey heated at 50-100 C has been reported (Fallico et al, 2004).…”
Section: Kinetic Calculationsmentioning
confidence: 56%
“…1 and 3). This can be attributed to complexity of non-enzymatic browning reactions because they involve different compounds and proceed through different chemical pathways depending on composition of product and processing conditions (Manzocco et al, 2001;Van Boekel, 2001). This behaviour could be also consequence of the formation of compounds with different antioxidant activity at various stages of Maillard reactions depending on treatment temperatures.…”
Section: Kinetic Calculationsmentioning
confidence: 99%
“…caramelisation) are the most important modifications that occur simultaneously during breakfast cereal manufacture. 15 Labelling experiments have shown that AA and FA formed in processed foods can be derived from sugar degradation (mainly from glucose and fructose, although disaccharides can also contribute to their formation) and from MR (from 1-deoxyglucosone and 3-deoxyglucosone). 16 The main reactants for MR and sugar caramelisation have been evaluated in order to gain knowledge on the genesis of AA and FA during the manufacture of breakfast cereals.…”
Section: Resultsmentioning
confidence: 99%
“…15 Heating of sugars alone gives rise to the formation of both FA and AA, although there could be an induction period for AA formation. However, when an amino acid is present, the FA level decreases considerably and AA becomes the predominant acid.…”
Section: Resultsmentioning
confidence: 99%
“…The elimination may even occur at such a high rate that no relevant acrylamide concentration build up or destroyed immediately after it is formed. It is generally accepted that the first stage of the actual Maillard reaction is the condensation of unprotonated amino group with reducing sugar in the open chain form resulting in a Schiff's base glycosylamine [17]. The rate of reaction between sugars and amino groups of amino acids is maximal at weakly acidic pH.…”
Section: Mechanism Of the Formation Of Acrylamidementioning
confidence: 99%